2014
DOI: 10.17576/jem-2014-4801-13
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital Accumulation and Economic Growth in Malaysia – Investigating the Long Run Nexus

Abstract: The endogenous growth theory emphasises that human capital is crucial to a country's economic growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Thus, confirming the existence of a long-run relationship between education expenditure and economic growth. Lai and Yussof (2014) examined the long-run relationship between human capital accumulation and economic growth in Malaysia from 1981 to 2010. The findings of their autoregressive distributed lag (ARDL) model revealed that there is significant long-run relationship between education level and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, confirming the existence of a long-run relationship between education expenditure and economic growth. Lai and Yussof (2014) examined the long-run relationship between human capital accumulation and economic growth in Malaysia from 1981 to 2010. The findings of their autoregressive distributed lag (ARDL) model revealed that there is significant long-run relationship between education level and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, confirming the existence of a longrun relationship between education expenditure and economic growth. Lai and Yussof (2014) examined the long run relationship between human capital accumulation and economic growth in Malaysia from 1981 to 2010. Empirical evidence from the autoregressive distributed lag (ARDL) model revealed that there is significant long run relationship between education level and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%